Study of Crash Scheme for Rural Employment (1971—74) - Planning Commission (Planning Commission, 1979)
The Government of India initiated during the early seventies several schemes for increasing employment opportunities in the country. Under this, Special Employment Programmes were launched during 1971-72 to 1973-74. A provision of Rs. 189 crores was made on schemes for educated unemployed and Rs. 140 crores M50 on schemes for generation of rural employment. The Programme Evaluation Organisation carried out in the year 1975 an evaluation study of these programmes. This report refers to evaluation of Crash Scheme for Rural Employment which has been the subject of great deal of interest. 1’he field work for this study was carried out by different units of the Programme Evaluation Organisation in the country. Several aspects such as formulation of schemes, execution of works, employment and wages generated, etc. have been examined. An attempt is also made to understand the pattern of participation by different groups particularly the weaker sections of the village community as also of the females.
Programme Evaluation Organisation Planning Commission Government of India